Diagnosis and monitoring of HIV (including resistance testing). (May 2018) - Patel, Sheel; Cassidy, Seán R.
Abstract: There are >100, 000 people living with human immunodeficiency virus (HIV) infection in the UK, a high proportion of whom remain undiagnosed. Fourth-generation HIV tests are the gold standard for diagnosing HIV infection, with a window period of 4 weeks from the point of infection. The assessment of a newly diagnosed HIV-positive patient should include a thorough history and examination to identify symptoms that might be related to opportunistic infection. Further investigations are required for all newly diagnosed patients to stage the infection and recommend appropriate antiretroviral therapy. Once the individual has started antiretroviral therapy, regular follow-up is crucial to ensure adherence to treatment.